Textile‐based sensors for electrical current measurement in three‐phase cables. Issue 1 (27th July 2021) - Strickland, Dani; Heinzel, Tincuta; King, Bee; Abedi Varnosfaderani, Mina; Zeidler, Alana; Seager, Rob
Abstract: There is much discussion about the implementation and benefits of smart electricity networks. However, the reality is that the instrumentation needed at low voltage is too expensive for large‐scale deployment. The most highly used monitoring systems in use today are based on Rogowski coil technology, which can only be used on single‐phase cables and terminations at £1k–£2k per substation. This study presents the results of novel research into modelling and analysis of a low‐cost sensor which can measure load on a 3 core cable at <£150 per substation. This study uses a new textile‐based sensor that can be produced by low‐cost, high‐volume manufacturing techniques. The study describes the modelling that is required in conjunction with the sensor geometry to be able to calculate the load current. Three textile‐based sensors of different dimensions were produced and tested and the results were compared with the current probe readings. The study shows that the textile sensors have an offset error of 14% but good linearity of 0.998, for around 10% of the cost of Rogowski coil technology.